Critérios de migração do processamento e armazenamento de dados da administração pública para a nuvem - Freitas, Pedro Henrique Chagas (2018)
The purpose of this research proposal is to verify migration criteria for the processing and storage of data from federal public administration to the cloud. An analysis of the scientific literature was carried out, pertinent to the topic and it is proposed to research with federal public managers of the area of information technology, in several organs of the Federal Executive power, with the use of semi-structured questionnaire. The proposed research will seek to point out the main criteria considered in the migration of data processing and storage to the cloud, according to the perception of the literature and the federal public managers, identifying the main factors of decision making in the migration to the cloud in the public administration federal government. Through the analysis of the literature, the knowledge relevant to the aspects that characterize the cloud paradigm will be raised, as well as the reasons that lead the organizations, whether or not to migrate to the cloud, thus creating the basis of the theoretical reference of the proposal of search. A semi-structured questionnaire for data collection will be used, together with federal public managers in the area of information technology, within the scope of the Federal Executive, allowing a better understanding of the criteria used for migration, the perception of public managers and the factors that influence the decision making process. deciding what to migrate to the cloud.